Pengaruh Penggunaan Media Pembelajaran Visual terhadap Minat Belajar Siswa dalam Pembelajaran Akidah Akhlak - Jeb Barianto; Hasrinal Hasrinal; Eline Yanty Putri Nasution (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
The background of the problem in this research is the lack of students’ learning interest, thelack of visual learning media, the lack of encouragement from the environment to increasestudent learning objectives in learning Aqidah Akhlak. This research problem is: (1) whetherthere is an influence of the use of visual learning media on students’ learning interest; (2) howmuch influence the use of visual learning media has on student learning interest. The purposeof this study is to determine the effect of visual media variabel (X) on learning interesrt (Y). Inthis study, data analysis used quantitative methods, namely by testing simple linear regressiondata instruments, and testing hypotheses data collection techniques using questionnaires bydistributing questionaires to 7 respondents in class VII student of Mutiara Al-Madani middleschool based on the results of the study, it can be concluded that there is a positive andsignificant influence between the variable use of visual learning media on students’ learninginterest in Aqidah Akhlak learning as evidenced by t count t table 3.409 2,571, while themagnitude of the influence between the use of visual learning media on student learninginterest Aqidah Akhlak learning is 69,8%.